Newspaper Clipping "California Girl Wins High Honor" (San Francisco Examiner, 1898)
Large paper clipping discussing the honor of Julia Morgan's acceptance to Ecole des Beaux Arts in Paris, the first woman in history to enter the architecture department there. Morgan was the third ranked of only ten foreign students admitted and ranked thirteenth across all applicants.